Reading shell shape: implications for palaeoenvironmental reconstructions. A case study for bivalves from the marine Quaternary of Argentina (south-western Atlantic) - Aguirre, Marina Laura (2015)
Most research on bivalves from the south-western Atlantic used morphological (shell) characters for taxonomic discriminations. Dominant Veneroids from Argentinian Quaternary coastal deposits exhibit wide morphological variation – often making objective discriminations difficult/impossible, which could be objectively described and compared through geometric morphometrics techniques. This work focuses on comparison of geometric morphometrics methods applied to fossil and modern shells, to assess inter- and intra-generic variations. Three approaches were considered: landmarks (L), semi-landmarks (SL) and outlines. Shell shape analyses for different time spans (Pleistocene, fossil Holocene and modern) and areas (Patagonia and Bonaerensian) showed that Elliptic Fourier analysis (EFA), Landmarks and Landmarks plus Semilandmarks (L þ SL) can discriminate at generic levels: Mactra, Mulinia (Mactridae) vs. Pitar, Protothaca, Eurhomalea, Clausinella (Veneridae). L and L þ SL are powerful for inter/intraspecific distinctions of Mactra. Variability of Mactra isabelleana includes the remaining nominal ‘species’ (transitional morphs). Causal environmental factors of (phenotype) variation could be addressed for modern environments (substrate, salinity and energy). Subtrigonal-inflated shells predominate in muddy, quieter, shallow mixo-polyhaline waters; ovate-elongate-compressed in sandy, poly-euhaline, deeper habitats. Differential spatial distribution (and abundance) across time responds to Late Quaternary high sea-level stands: transgressive maxima allowed higher salinity in marginal-marine areas and optimal conditions for Mactra isabelleana contrasting with scarcer records in the Mar Argentino today.